Work Department and Workplace Stress: A Cross-Sectional Study on Health Office Employees - Albadii, Haidar Rifqi; Hananingtyas, Izza (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: Work-related stress has become a critical issue in the health sector, with significant impact on productivity and quality of service. Preliminary studies found that 50% of employees at the Health Office of City X experienced work stress. This study aimed to investigate the association between gender, age, department, and stress among health workers in the Health Office of X city.Methods: A cross-sectional study was conducted among 115 Health Office employees in City X in February- July 2025, which has already fullfill the minimal sample size for two proportion hypothesis with alpha of 0.05 and 95% power. The subjects were from five departments in the Health Office. Data were collected through interviews using valid and reliable structured questionnaires of the Workplace Stress Scale. Analyses were performed using chi-square tests and logistic regression.Results: Overall, 53% of respondents experienced work-related stress. Older subjects (≥30 years) experienced more stress than younger workers, with an OR of 2.4 (95% CI: 1.04-5.56; p=0.038). Workers in the Division of Disease Prevention and Control also experienced more stress, with an OR of 3.56 (95% CI:1.13 – 11.11; p=0.030), while those in the other departments did not. No significant relationship was found between gender and work stress (p =0.552).Conclusion: Work stress mitigation for employees can be implemented through interventions such as cross-generational mentoring programs and workload evaluation. Additionally, it is necessary to conduct regular assessments of work stress, stress management training, and monitor the workload of all employees in the Health Department.